Рамковий концепт оцінювання екосистемних активів територіальних громад - Веклич, О. (Економіка природокористування і сталий розвиток, 2021)
Уперше у фаховій літературі розкрито та представлено теоретико-методологічну композицію об’ємної моделі рамкового концепту оцінювання екосистемних активів територіальних громад, яка формує загальний концептуальний базис і логістичний алгоритм практичних дій щодо впровадження процесу такого оцінювання в управління природокористуванням. Відповідно до існуючої типологізації концептів наведено характеристику концепт-фрейма оцінювання екосистемних активів територіальних громад; розкрито ієрархію понятійного базису його становлення, що спирається на вихідний та опорний понятійний базис концепту екосистемної складової природного капіталу, а також концептів екосистемних активів і екосистемних послуг.
Висвітлено основні репрезенти процесу побудови моделі рамкового концепту оцінювання екосистемних активів територіальних громад за відповідним логістичним алгоритмом її композиції, що має здійснюватись кількома послідовними ітераціями. Перша – аналіз і структурно-функціональний опис понятійного базису концепту екосистемних активів як продуцентів екосистемних послуг, що репрезентує досліджуваний фрейм-концепт. Друга ітерація передбачає поглиблене розкриття змістовного наповнення та ознак екосистемних активів територіальних громад як поняття. Третя – полягає в наданні опису способів оцінювання екосистемних активів територіальних громад як двовимірного формоутворення, забезпечуючи відповідний рівень його деталізації. Четверта ітерація – це подання змістової сфери екосистемних активів (формальної системи) у форматі числення, тобто визначення їх числової формалізації, зокрема вартісного виміру екосистемних активів як продуцентів екосистемних послуг. П’ята – дослідження сценаріїв оцінювання екосистемних активів територіальних громад.
У підсумку створюється теоретико-методологічна платформа розуміння вченими і практиками обґрунтування вибору та імплементація відповідних практичних заходів щодо оцінювання екосистемних активів, належних конкретним територіальним громадам. For the first time in the professional literature the theoretical and methodological composition of the three-dimensional model of the frame-concept of assessment of ecosystem assets of territorial communities is revealed and presented. This frame-concept forms the general conceptual basis and logistic algorithm of practical actions for implementation the assessment of ecosystem assets of territorial communities in the practice of nature management. In accordance with the existing typology of concepts, the characteristics of the frame-concept of assessment of ecosystem assets of territorial communities are given.
The main elements of the three-dimensional model of the frame-concept of assessment of ecosystem assets of territorial communities, which are identified by its construction according to the appropriate logistic algorithm of its composition, are established. This algorithm should be performed in several successive iterations. The first is the analysis and structural-functional description of the categorical basis of the concept of ecosystem assets as producers of ecosystem services, which represents the studied frame-concept. The second iteration involves in-depth disclosure of the content and features of ecosystem assets of territorial communities as a notion. The third is to describe ways to assess the ecosystem assets of local communities as a two-dimensional formation, providing an appropriate level of detail. The fourth iteration is the definition of the numerical formalization of the semantic sphere of ecosystem assets, in particular the numerical formalization of the value measurement of ecosystem assets as producers of ecosystem services. The fifth is a study of scenarios for assessing the ecosystem assets of local communities.
The subject-object and other components of the scenario of assessment of ecosystem assets of a particular territorial community, which are written in its corresponding scheme, are shown. In the future, this, in turn, allows us to design the nature of the relationship between the local community as the owner of ecosystem assets and other beneficiaries of their use. This will make it possible to address the level of responsibility for the functioning of the ecosystem assets that produce these services, as well as when considering eco-compensation for the consumption of specific types of ecosystem services or their loss.
As a result, the study of the frame-concept of assessment of ecosystem assets of territorial communities created an appropriate theoretical and methodological platform that forms its holistic view and understanding by scientists and practitioners. Therefore, it will help to justify and implement real management measures to assess ecosystem assets belonging to specific local communities.